KEABSAHAN PERNYATAAN PELEPASAN HAK MENUNTUT RESTITUSI PAJAK PADA PEMBATALAN TRANSAKSI JUAL BELI - Arjun Arjun; Anwar Borahima; Nurfaidah Said (Faculty of Law, Universitas Riau, 2018)
This study aims to analyze the validity of declaration of release of the right to demand tax refund BPHTB on tax validation application and Legal protection for applicant tax refund BPHTB on cancellation of Sale and Purchase transactions. This research is done by using normative juridical research method with approach of legislation and also conceptual approach (conceptual approach). The results of this study indicate that: 1) Validity Letter Statement Release of rights according to tax restitution BPHTB in tax validation application in this case the Statement does not provide legal certainty. ) Legal protection for applicant tax refund BPHTB on cancellation of sale transactions purchase may be made pursuant to Ministerial Regulation No. 187 / PMK.03 / 2015 stating that the application for refund of tax overpayment should not be payable.Keywords : BPHTB, Restitution